THE ANALYSIS OF TWO PRE-READING STRATEGIES: CONTEXTUAL REDEFINITION AND WORD LIST IN EFL LEARNERS’ READING COMPREHENSION - Nika Asri (Journal of English and Education, 2013)
This study aimed to examine which of the two pre-reading strategies, contextual redefinition or word list, is more effective for EFL learners’ reading comprehension. In addition, it was aimed at investigating students’ responses to the use of both strategies. The research design used in this study was counterbalanced. Two intact classes at eight-graders in a junior high school in Bandung were chosen based on the similarity of pre-test mean score. Both quantitative and qualitative methods were used in the process of collecting the data. The quantitative data were obtained from the post-tests. Moreover, qualitative data were gained from questionnaires and interview. The results of the study revealed that contextual redefinition was more effective to be used than word list as pre-reading strategy in reading comprehension. It can be seen from the mean score of the first and the second post-test. The mean score of the students who received contextual redefinition strategy outperformed the mean score of the students who experienced word list strategy (72.1361.47 and 76.5371.23). Moreover, the analysis showed that more than half students in group A (56%) and group B (55%) liked to use contextual redefinition better. This was due to the consideration that contextual redefinition could enhance new vocabularies, stimulate language schema, stimulate students’ interest to the words that will be studied, and help the students to decode the difficult terms. Although the findings revealed that students preferred to use contextual redefinition, it is interesting to note that significant number of students also acknowledge the importance of the use of word list as pre-reading strategy. In fact, the students in group A (44%) and group B (45%) argued that the use of word list as pre-reading strategy was easier than contextual redefinition. On the basis of the findings, it is recommended that teachers should benefit from a variety of pre-reading strategies, and one of the alternative pre-reading strategies in helping EFL learners’ reading comprehension is contextual redefinition. Keywords:Contextual Redefinition, Word List, EFL Learners, and Reading Comprehension